Delito y especialización en Chile - Fábrega Lacoa, Jorge (Política criminal, 2014)
What crime recurs with recidivism? This paper analyses the patterns of recidivism among the population sentenced to imprisonment in Chile. For this purpose, subgroups of offenders who specialize in each type of crime are identified. The analysis is based on data of imprisonment between 2007 and 2010 provided by the Chilean Gendarmerie. The results indicate that 65% of the recidivist population will specialize in some criminal category. Three of seventeen possible categories (burglary, theft and nonviolent robbery) concentrate 50% of criminal specialization. There were statistically significant differences in levels of specialization by age and gender of the offender. Finally, the probability that an offender is specialized in one type of criminal category tends to one after his third recidivism.